1995
DOI: 10.1080/07448481.1995.9940476
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Discussion of Psychosocial Issues at Student Health Visits

Abstract: In a pilot study, the authors distributed a brief questionnaire dealing with psychosocial concerns to 200 students awaiting treatment in the student health service at a large urban university. They hypothesized that a questionnaire administered immediately before students visited the physician or family nurse practitioner would encourage the students to discuss problems such as anxiety and depression during the medical session. Using the questionnaire, they found, led to the practitioner's discovery of a condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…Consistent with previous research in college settings (Cowan & Morewitz, 1995), we found a twofold increase in the discussion of behavioral problems when health care providers used the questionnaire. This discussion facilitated assessment of the need for treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous research in college settings (Cowan & Morewitz, 1995), we found a twofold increase in the discussion of behavioral problems when health care providers used the questionnaire. This discussion facilitated assessment of the need for treatment.…”
Section: Discussionsupporting
confidence: 90%
“…To date, the need for integrated care has not been effectively empirically examined in the campus health care setting. Although Cowan and Morewitz (1995) found that using questionnaires in college health care increased dialogue about student-patients' psychosocial concerns, they did not evaluate resulting changes in medical providers' choice of interventions. Assessing for implementation of behavioral interventions is important as patients suffering from disorders like depression, generalized anxiety, phobias, and obsessive-compulsive disorder typically delay seeking help for up to a decade (Bailey, 2005).…”
mentioning
confidence: 99%
“…Loganbill et al (1982), and Schwitzer (1996;1997) found that when new clinicians were instructed in the four-step case-conceptualization format applying theory to practice, they went on to spontaneously use the approach and bring it with them into supervision sessions. Cowan and Morewitz (1995) similarly found in the college student health field that when practitioners were provided a more structured model for intake and problem identification, they more effectively identified patient concerns on a routine basis. Anecdotal evidence also shows that learners exposed to popular character cases during training later received consistent, unusually high ratings from supervisors for their case conceptualization skills.…”
Section: Limitationsmentioning
confidence: 92%
“…We suggested using written measures (such as the DES) and clinical interview protocols (such as the DDIS and the SCID-D-R) as tools for determining whether some student clients might be experiencing dissociation symptoms and even a dissociative disorder along with their more common presentations of anxiety, mood, and psychotic symptoms, as well as substance use concerns. Cowan and Morewitz (1995) found that when college health center staff were given a mental health checklist to use as a tool for identifying counseling issues among their clients, they were much more likely to identify their students' mental health and wellness needs and make appropriate interventions or referrals. Likewise, we think that if college counselors become more aware of DID and consider using screening and diagnostic tools related to the disorder, they will be more likely to identify situations in which students might be dealing with this complex mental health problem.…”
Section: College Counseling Limitations and Didmentioning
confidence: 99%